The Effectiveness of Mauro Method Qur'an Memorization: A Study on Children with Autism Spectrum Disorders - Risca Amani; Rahmahtrisilvia Rahmahtrisilvia; Arisul Mahdi; Afdal Luthfi; Fitri Maulidazani; Vikri Aflaha Qomari; Azmil Umur (Ta'dib, 2024)
Everyone has the right to study and memorize the Qur'an, including children with autism spectrum disorders. Despite having difficulty communicating, autistic children can to memorize the Quran by applying various methods, such as Mauro. The Mauro method is a combination of the method of memorizing the Qur'an by listening, seeing, and repeating. The purpose of this study is to see impact of the application of the Mauro method in helping the process of memorizing the Qur'an for children with autism spectrum disorders, especially in short surahs. The type of research used is an experiment in the form of Single Subject Research (SSR) with an A-B-A design. The study was conducted in 14 meetings with 3 subjects. The results of the data analysis proved that the ability to read short surahs in autistic children increased because of the intervention given, namely the Mauro method. The continuous application of the Mauro method can assist in the process of memorizing short surahs for children with autism spectrum disorders.